Impact tracking: a practitioner-developed approach to scaling agricultural innovation in Ethiopia - Child, K.; Desta, G.; Douthwaite, Boru; Haileslassie, Amare; Rooyen, Andre F. van; Tamene, Lulseged D.; Uhlenbrook, Stefan (International Water Management Institute, 2021)
This paper argues for more creativity and flexibility in agricultural research for development (AR4D) scaling and impact evaluation in complex contexts. While acknowledging the importance of setting reasonable end-of-project targets and outcomes, we argue that the achievement of outcomes and impacts, particularly in complex contexts, requires adaptive management and acknowledgment that significant positive outcomes and impacts may occur after the project funding cycle is complete. The paper presents a practitioner-developed approach to scaling AR4D innovations called Impact Tracking (IT). We illustrate IT in practice by presenting three case studies from Ethiopia in which IT proved crucial to achieving impact. The paper concludes by drawing lessons from the case studies and discussing what implications IT may have for development practitioners.